2014
DOI: 10.17584/rcch.2013v7i2.2237
|View full text |Cite
|
Sign up to set email alerts
|

Variability in the nutraceutical properties of fenugreek (Trigonella foenum-graecum L.) sedes

Abstract: Variability in the nutraceutical properties of fenugreek (Trigonella foenum-graecum L.) seedsVariabilidad de las propiedades nutracéuticas de la alholva (Trigonella foenum-graecum L.)Variability in seeds size and colour of different genotypes of fenugreek. Foto: K.P. Singh ABSTRACTFenugreek (Trigonella foenum-graecum L.) leaves and seeds have been used extensively for medicinal purposes. Fenugreek seed is known to exhibit anti-diabetic properties and effects such as hypocholesterolaemic, anticancerous and thyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Giridhar and Sarada (2009) reported significant differences among different yield attributes and yield in rainfed vertisols of Krishna-Godavari Zone of Andhra Pradesh. Seeds pod -1 , test weight, number of pods plant -1 , branches plant -1 and plant height were the important characters for selection of high yielding lines as they exhibited direct and positive effect on seed yield per plant (Sharma and Sastry, 2008;Pushpa et al, 2012;Singh et al, 2013). Higher seed yield in fenugreek always associated with the higher number of branches, pods plant -1 , seeds pod -1 (Datta and Chatterjee, 2014;Singh et al, 2012), through better expression of associated physiological traits (Banafar, 2000).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Giridhar and Sarada (2009) reported significant differences among different yield attributes and yield in rainfed vertisols of Krishna-Godavari Zone of Andhra Pradesh. Seeds pod -1 , test weight, number of pods plant -1 , branches plant -1 and plant height were the important characters for selection of high yielding lines as they exhibited direct and positive effect on seed yield per plant (Sharma and Sastry, 2008;Pushpa et al, 2012;Singh et al, 2013). Higher seed yield in fenugreek always associated with the higher number of branches, pods plant -1 , seeds pod -1 (Datta and Chatterjee, 2014;Singh et al, 2012), through better expression of associated physiological traits (Banafar, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…The high yielding genotypes LFC-103 (0.72 %) and HM-348 (0.89 %) had significantly lower diosgenin content compared to the local cultivar. Singh et al (2013) reported wide diversity among fenugreek germplasm lines regarding the steroid sapogenin contents. Depending upon geographic origin, genotypes, environmental factors and management, diosgenin contents in fenugreek were reported to vary between 0.3 and 2.0% (Fazli and Hardman, 1968;Puri et al, 1976;Sharma and Kamal, 1982;Kamal et al, 1987;Taylor et al, 2002;Acharya et al, 2006).…”
Section: Diosgenin Content and Productivitymentioning
confidence: 99%
“…The highest 100 seed weight of 2.55g was recorded in Ajmer Methi 1 which was on par with DFC 1, DFC 11, DFC 25 and Ajmer Methi 2 and these were also on par with the check Gujarat Methi 2. Seeds per pod, test weight, number of pods per plant, branches per plant and plant height were the important characters for selection of high yielding lines as they exhibited direct and positive effect on seed yield per plant (Sharma and Sastry, 2008;Pushpa et al, 2012;Singh et al, 2013;Jain et al,2014).…”
Section: Resultsmentioning
confidence: 99%
“…Further they reported that seeds of all the spices and herbs showed high amount of potassium (383 to 823 mg/100g), calcium (75 to 270 mg/100g), magnesium (42 to 102 mg/100g) and iron (20.5 to 65 mg/100g) whereas low levels of zinc, manganese and copper. Singh et al, (2013) in a study on variability in nutraceutical properties of fenugreek revealed that chemical constituents of seeds of various fenugreek genotypes viz. Saponin, protein, moisture %, ash, fiber, Zn, Fe, Mn, and Mg contents differed considerably and such variability should not be overlooked or underestimated in research trials.…”
Section: Nutrient Profilementioning
confidence: 99%